1998
DOI: 10.1083/jcb.142.6.1461
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Muscular Dystrophy in α-Sarcoglycan–deficient Mice

Abstract: Limb-girdle muscular dystrophy type 2D (LGMD 2D) is an autosomal recessive disorder caused by mutations in the α-sarcoglycan gene. To determine how α-sarcoglycan deficiency leads to muscle fiber degeneration, we generated and analyzed α-sarcoglycan– deficient mice. Sgca-null mice developed progressive muscular dystrophy and, in contrast to other animal models for muscular dystrophy, showed ongoing muscle necrosis with age, a hallmark of the human disease. Sgca-null mice also revealed loss of sarcolemmal integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
384
4
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(413 citation statements)
references
References 57 publications
19
384
4
4
Order By: Relevance
“…[33][34][35] It has been shown that deficiency in these proteins makes the membrane vulnerable and renders it prone to tears during contraction. [36][37][38] This membrane leakage induces abnormal calcium influx followed by activation of the ubiquitous calpains, leading to an excess of unwanted and untimely proteolysis, and finally necrosis of the muscle fiber. [39][40][41] Accordingly, the high numbers of central nuclei found in both models indicate an ongoing cycle of necrosis and regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] It has been shown that deficiency in these proteins makes the membrane vulnerable and renders it prone to tears during contraction. [36][37][38] This membrane leakage induces abnormal calcium influx followed by activation of the ubiquitous calpains, leading to an excess of unwanted and untimely proteolysis, and finally necrosis of the muscle fiber. [39][40][41] Accordingly, the high numbers of central nuclei found in both models indicate an ongoing cycle of necrosis and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The construction and characterization of this model has been previously described. 37 The dystrophin-deficient mdx model and the normal controls, C57Bl/6 and C57Bl/10, were purchased from Charles River Laboratories (Les Oncins, France). Mice of specified age were used for intramuscular injection of recombinant AAV.…”
Section: In Vivo Vector Delivery Into Muscle Tissuementioning
confidence: 99%
“…[21][22][23] In addition, we recently reported preliminary data on adenovirus-mediated delivery of ␣-SG to the skeletal muscle of mice lacking this protein and displaying a progressive muscular dystrophy closely mimicking the human LGMD 2D pathology. 24 Just as with ␦-SG, ␣-SG gene transfer restores the expression of the other sarcoglycan proteins at the sarcolemma of transduced fibers. [21][22][23][24] In this study, we present extensive data supporting the feasibility of an ␣-SG gene transfer approach to prevent the dystrophic process in Sgca-null mice.…”
Section: Introductionmentioning
confidence: 99%
“…There are both sarcoglycan null mouse models, as well as a mouse model with a disease-specific missense mutation. [52][53][54][55][56][57] The sarcoglycan null mice and the delta sarcoglycan-deficient cardiomyopathic hamsters (BIO14.6, BIO53.58, CHF147, TO-2) are also wellestablished animal models for sarcoglycan-deficient cardiomyopathy. The spectrum of therapeutic approaches that has been used to treat the dilated cardiomyopathy in the hamster models is very broad and reaches from classical pharmacotherapy approaches 58,59 to gene replacement therapy, 60 -62 cellular therapies, [63][64][65] and recombinant growth factor therapies.…”
Section: Sarcoglycan-deficient Lgmd2c-2fmentioning
confidence: 99%